Restrictive vs liberal oxygen for trauma patients‐the TRAUMOX1 pilot randomised clinical trial. Issue 7 (25th March 2019) - Baekgaard, Josefine S.; Isbye, Dan; Ottosen, Camilla Ikast; Larsen, Mo Haslund; Andersen, Jakob Hessel; Rasmussen, Lars S.; Steinmetz, Jacob
Abstract : Introduction: Hyperoxaemia is commonly observed in trauma patients but has been associated with pulmonary complications and mortality in some patient populations. The objectives of this study were to evaluate whether maintenance of normoxia is feasible using a restrictive oxygen strategy in the initial phase after trauma and to evaluate the incidence of 30‐day mortality and/or major pulmonary complications. Methods: Forty‐one adult trauma patients admitted to our trauma centre were randomised to 24 hours of restrictive oxygen therapy (no supplemental oxygen if the arterial oxyhaemoglobin saturation (SpO2 ) was at least 94%, n = 21) or liberal oxygen therapy (intubated patients: FiO2 1.0 in the trauma bay, 0.8‐1.0 elsewhere; spontaneously breathing patients: 15 L/min via a non‐rebreather mask, n = 20). Two blinded anaesthesiologists evaluated major in‐hospital pulmonary complications within 30 days. Results: Protocol compliance was high, as the median arterial oxygen tension was significantly lower in the restrictive group (10.8 kPa [9.7‐12.0] vs 30.4 kPa [23.7‐39.0], P < 0.0001). There were seven episodes of SpO2 below 90% in the restrictive group and one episode in the liberal group. Thirty‐day mortality and/or major in‐hospital pulmonary complications occurred in 4/20 (20%) in the restrictive group and in 6/18 (33%) in the liberal group: two patients in each group died within 30 days and the incidence of major in‐hospital pulmonary complications was 2/20 (10%) in the restrictive group and 4/18 (22%) in the liberal group. Conclusion: Maintenance of normoxia using a restrictive oxygen strategy following trauma is feasible. This pilot study serves as the basis for a larger clinical trial.